Analysis Of Primigravida On Knowledge And Behaviour About Vct In Marie Stopes Clinic Timor Leste - Brigita Lutan; Yulidia Tiani; Asri Dewi Wahyuningtyas (Universitas STRADA Indonesia, 2023)
PMTCT (Preventing from mother to Child transmision) is one of the methods to prevent HIV transmission from mother to baby. To support this program, a VCT ( Voluntary Counseling Test) is performed on all primigravidas when carrying out Antenatal Care. The phenomenon that occurred was found that there were still primigravida who did not perform VCT examination during Antenatal Care visits. So it is very important to analyze the level of knowledge of primigravida mothers about VCT and VCT examination behavior at the Marie Stopes Clinic, Timor Leste. The research design was analytic with a cross-sectional design. The population was all primigravida mothers who visited the Marie Stopes Clinic. The research design was analytic with a cross-sectional design. The population was all primigravida mothers who visited the Marie Stopes Clinic, totaling 87 people, while the research sample were 34 people. The researcher used accidental sampling to measure research sample. Observational sheet and questionnaire were used to collect the data. Data was analyzed by Chi Square Statistical Test with (p.value = 0.001) that means there was a relationship between primigravida’s knowledge about VCT and behavior to do VCT examination. Factors which play an important role in supporting knowledge of primigravida were age, education and occupation. In addition, health workers take a greatly part in supporting this program, therefore it is expected that health workers will continue to implement integrated antenatal care services especially VCT examination for pregnant woman.